Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the equation
[tex]\[ \frac{8}{y - 2} = \frac{4}{4y + 6} \][/tex]
we need to find the value of [tex]\( y \)[/tex] that satisfies it. Follow these steps to solve it:
1. Cross-Multiply: When we have an equation of the form [tex]\( \frac{a}{b} = \frac{c}{d} \)[/tex], we can cross-multiply to get
[tex]\[ a \cdot d = b \cdot c \][/tex]
Applying this to our equation:
[tex]\[ 8 \cdot (4y + 6) = 4 \cdot (y - 2) \][/tex]
2. Distribute: Distribute the constants through the parentheses:
[tex]\[ 8 \cdot 4y + 8 \cdot 6 = 4 \cdot y - 4 \cdot 2 \][/tex]
[tex]\[ 32y + 48 = 4y - 8 \][/tex]
3. Isolate [tex]\( y \)[/tex]: Let's collect all terms involving [tex]\( y \)[/tex] on one side of the equation and constant terms on the other side:
[tex]\[ 32y + 48 = 4y - 8 \][/tex]
Subtract [tex]\( 4y \)[/tex] from both sides:
[tex]\[ 32y - 4y + 48 = -8 \][/tex]
[tex]\[ 28y + 48 = -8 \][/tex]
Subtract 48 from both sides:
[tex]\[ 28y = -8 - 48 \][/tex]
[tex]\[ 28y = -56 \][/tex]
4. Solve for [tex]\( y \)[/tex]: Divide both sides by 28:
[tex]\[ y = \frac{-56}{28} \][/tex]
[tex]\[ y = -2 \][/tex]
Therefore, the solution to the equation is
[tex]\( y = -2 \)[/tex]
Hence,
[tex]\[ y = -2 \][/tex]
[tex]\[ \frac{8}{y - 2} = \frac{4}{4y + 6} \][/tex]
we need to find the value of [tex]\( y \)[/tex] that satisfies it. Follow these steps to solve it:
1. Cross-Multiply: When we have an equation of the form [tex]\( \frac{a}{b} = \frac{c}{d} \)[/tex], we can cross-multiply to get
[tex]\[ a \cdot d = b \cdot c \][/tex]
Applying this to our equation:
[tex]\[ 8 \cdot (4y + 6) = 4 \cdot (y - 2) \][/tex]
2. Distribute: Distribute the constants through the parentheses:
[tex]\[ 8 \cdot 4y + 8 \cdot 6 = 4 \cdot y - 4 \cdot 2 \][/tex]
[tex]\[ 32y + 48 = 4y - 8 \][/tex]
3. Isolate [tex]\( y \)[/tex]: Let's collect all terms involving [tex]\( y \)[/tex] on one side of the equation and constant terms on the other side:
[tex]\[ 32y + 48 = 4y - 8 \][/tex]
Subtract [tex]\( 4y \)[/tex] from both sides:
[tex]\[ 32y - 4y + 48 = -8 \][/tex]
[tex]\[ 28y + 48 = -8 \][/tex]
Subtract 48 from both sides:
[tex]\[ 28y = -8 - 48 \][/tex]
[tex]\[ 28y = -56 \][/tex]
4. Solve for [tex]\( y \)[/tex]: Divide both sides by 28:
[tex]\[ y = \frac{-56}{28} \][/tex]
[tex]\[ y = -2 \][/tex]
Therefore, the solution to the equation is
[tex]\( y = -2 \)[/tex]
Hence,
[tex]\[ y = -2 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.